Eyes that kiss in the corners - Ho, Joanna; Ho, Dung (New York : Harper, 2021)
A young Asian girl notices that her eyes look different from her peers. They have big, round eyes and long lashes. She realizes that her eyes are like her mother's, her grandmother's, and her little sister's. They have eyes that kiss in the corners and glow like warm tea, crinkle into crescent moons, and are filled with stories of the past and hope for the future. Drawing from the strength of these powerful women in her life, she recognizes her own beauty and discovers a path to self love and empowerment.
School Library Journal starred, December 2020
2.5
K-3
Some copies purchased with funds from CPSF Equity Grant - 2022.
Keywords: Asian Americans -- Juvenile fiction; Eye -- Juvenile fiction; Families -- Juvenile fiction; Self-acceptance -- Juvenile fiction; Asian Americans -- Juvenile fiction; Eye -- Fiction; Family life -- Fiction; Self-acceptance -- Fiction